Filtration membrane and method for producing the same
A crosslinked cationic and anionic hydrophilic polymer coating on filtration membranes addresses fouling resistance issues, providing effective fouling resistance and cost-efficient industrial scalability.
Patent Information
- Application Number
- JP2023106749
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing filtration membranes face challenges with membrane fouling due to the adhesion of organic matter, requiring costly chemical and physical cleaning, and existing methods to enhance fouling resistance, such as using zwitterions, are difficult to industrialize and costly.
A filtration membrane is developed with a coating containing a crosslinked mixture of cationic and anionic hydrophilic polymers on its surface, which mimics the fouling-resistant properties of zwitterions without the need for complex polymerization methods, allowing for industrial scalability and versatility.
The membrane exhibits excellent fouling resistance, maintaining high performance and reducing the need for frequent cleaning, thus lowering operational costs and enhancing its applicability to various filtration applications.
Smart Images

Figure 2025006139000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a filtration membrane and a method for producing the same. [Background technology]
[0002] Separation techniques using filtration membranes have advantages such as the compactness of the equipment, and are therefore widely used in a variety of fields, for example, in the water treatment field, such as water purification, drinking water production, industrial water production, and wastewater treatment, the food industry, and pharmaceutical manufacturing.
[0003] In separation technologies using filtration membranes, a phenomenon known as membrane fouling occurs, in which organic matter such as particles and proteins adhere to the surface of the filtration membrane, resulting in a decrease in filtration capacity. Membrane filtration is operated while suppressing the occurrence of membrane fouling by periodically repeating chemical cleaning using chemicals and physical cleaning using air and water. However, the costs of chemical cleaning and physical cleaning required for membrane filtration operation are high, and there is a demand for filtration membranes with high fouling resistance that are less susceptible to the adhesion of particles and proteins and that fundamentally suppress membrane fouling.
[0004] Various studies have been conducted on the fouling resistance of such filtration membranes. Specifically, it is said that it is preferable to increase the hydrophilicity of the membrane in order to improve the fouling resistance, and for example, it has been considered to coat the membrane with a hydrophilic resin to increase the hydrophilicity of the membrane. For example, Patent Document 1 discloses a porous hollow fiber filtration membrane coated with a polyvinyl alcohol resin.
[0005] In recent years, it has been described that the fouling resistance of membranes can be further improved by using polymer materials having a zwitterion structure. For example, Non-Patent Document 1 describes, from the viewpoint of biomimetics, that by mimicking the zwitterion structure in cell membranes and forming a hydration structure with water molecules on the membrane surface, adhesion of organic matter such as particles and proteins can be suppressed and fouling resistance can be improved. In addition, Non-Patent Document 2 describes that when the membrane surface of a polysulfone membrane is coated with a polymer having zwitterions by a graft polymerization method, the amount of adhesion of proteins and the like is reduced and fouling resistance is improved. Furthermore, Patent Document 2 discloses a composition containing a vinylidene fluoride polymer and a zwitterionic site as a material for a filtration membrane, and a porous membrane using the composition. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2015 / 008668 [Patent Document 2] Special Publication No. 2023-506230 [Non-patent literature]
[0007] [Non-Patent Document 1] Acta Biomaterialia, August 2016, Vol.40, p.142-152 [Non-Patent Document 2] Journal of Membrane Science, November 1, 2013, Vol.446, p.79-91 Summary of the Invention [Problem to be solved by the invention]
[0008] The technology described in Patent Document 1 (technology for coating the membrane surface of a filtration membrane with a hydrophilic polymer material) has been put to practical use in many places, is easy to mass-produce industrially, and is applicable to existing filtration membranes, making the technology applicable in a wide range. However, Patent Document 1 does not discuss the use of a polymer material having a zwitterion structure as described above, and it is believed that fouling resistance can be further improved if the membrane surface of a filtration membrane can be coated with a zwitterion.
[0009] On the other hand, the above-mentioned Non-Patent Documents 1 and 2 disclose that anti-fouling properties can be improved by coating the filtration membrane surface with zwitterions, but the membrane surface coating methods described in these documents require a special multi-stage polymerization method that requires advanced laboratory-level control, such as a graft polymerization method, and have the problem that they are difficult to industrialize or mass-produce. Therefore, it is difficult to put filtration membranes with their membrane surfaces coated with zwitterions into practical use in society.
[0010] In Patent Document 2, efforts are being made to industrialize the effects of these zwitterions in order to put them to practical use in society. However, since there is a concern that the presence of zwitterions in the composition, which is the material of the filtration membrane, may cause a decrease in chemical strength, physical strength, and polymer crystallinity during the formation of the filtration membrane, it is difficult to manufacture a practical filtration membrane. In addition, the composition of Patent Document 2 is expected to have high manufacturing costs, and its social implementation in filtration membranes is also disadvantageous in terms of manufacturing costs. Furthermore, since this is not a technology with a view to coating the membrane surface of commercially available filtration membranes or already manufactured filtration membranes, it is also an issue that the versatility of the technology is very low.
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a filtration membrane having excellent anti-fouling properties without using zwitterions, and a method for producing the same. [Means for solving the problem]
[0012] A filtration membrane according to one embodiment of the present invention is a filtration membrane for water treatment, and has a coating containing a crosslinked mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties on at least the membrane surface that comes into contact with the water to be treated.
[0013] It is also preferred that the hydrophilic polymer having cationic properties contains a monomer unit having a cationic group in the molecular chain, and the content of the monomer unit having the cationic group is 0.1 mol % or more relative to the total number (100 mol %) of monomer units constituting the hydrophilic polymer having cationic properties, and that the hydrophilic polymer having an anionic property contains a monomer unit having an anionic group in the molecular chain, and the content of the monomer unit having the anionic group is 0.1 mol % or more relative to the total number (100 mol %) of monomer units constituting the hydrophilic polymer having anionic properties.
[0014] Furthermore, it is preferable that the hydrophilic polymer having cationic properties is a cationically modified polyvinyl alcohol, and the hydrophilic polymer having anionic properties is anionically modified polyvinyl alcohol.
[0015] It is also preferable that the zeta potential of the membrane surface having the coating is −5 mV or more and 15 mV or less.
[0016] Furthermore, the ratio by mass of the hydrophilic polymer having cationic property to the hydrophilic polymer having anionic property in the mixture is preferably 2:98 to 98:2.
[0017] Furthermore, a method for producing a filtration membrane according to a further aspect of the present invention includes a preparation step of preparing a coating solution containing a mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties, a coating formation step of contacting at least a membrane surface of a filtration membrane for water treatment, which is in contact with the treatment water, with the coating solution to form a coating on the membrane surface, and a crosslinking step of crosslinking the mixture of the hydrophilic polymer having cationic properties and the hydrophilic polymer having anionic properties after the coating formation step. Effect of the Invention
[0018] According to the present invention, it is possible to provide a filtration membrane having excellent anti-fouling properties without using zwitterions, and a method for producing the same. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a graph showing the results of the evaluation of anti-fouling properties in Examples 1 and 2 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these.
[0021] <Filtration membrane> The filtration membrane in this embodiment is a filtration membrane for water treatment, and has a coating containing a crosslinked mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties on at least the membrane surface that contacts the treated water. With this configuration, a filtration membrane having excellent fouling resistance can be obtained without using zwitterions. Furthermore, when producing such a filtration membrane, a commercially available filtration membrane or a filtration membrane that has already been produced can be used as the base material constituting the filtration membrane, so that a filtration membrane having fouling resistance can be produced by a simple production method, and the technology has high versatility.
[0022] The filtration membrane of the present embodiment includes a substrate and the coating as described above. First, the substrate will be specifically described.
[0023] [Base material] (shape) The substrate constituting the filtration membrane in this embodiment is a filtration membrane for water treatment, and the type is not particularly limited. For example, flat membrane, tubular type, hollow fiber membrane type, spiral type, nonwoven fabric, etc. are known, and among these, the hollow fiber membrane type is preferred because it has a large membrane area and excellent filtration performance.
[0024] (material) The material of the substrate is not particularly limited as long as it is a material capable of forming a filtration membrane, and examples thereof include fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride, acrylic resins, polyacrylonitrile, polystyrene, polyamide, polyacetal, polycarbonate, polyphenylene ether, polyphenylene sulfide, polyethylene terephthalate, polyetherimide, polyamideimide, polychloroethylene, polyethylene, polypropylene, crystalline cellulose, polysulfone, polyphenylsulfone, polyethersulfone, acrylonitrile butadiene styrene (ABS) resin, acrylonitrile styrene (AS) resin, and copolymers thereof. In addition, a filtration membrane made of an inorganic material such as zeolite or ceramic can also be used as the substrate. As the material resin of the substrate, among the resins exemplified above, polyvinylidene fluoride and polysulfone are preferred because they are widely used as filtration membranes.
[0025] (pore diameter) The pore size of the substrate is not particularly limited, and is preferably 20 μm or less and 0.001 μm or more, more preferably 20 μm or less and 0.005 μm or more, and even more preferably 20 μm or less and 0.01 μm or more.
[0026] When the pore size is 20 μm or less, membrane fouling due to adhesion of proteins and fine particles is likely to occur. Therefore, the effect of the present invention is more pronounced when the pore size is in the range of 20 μm or less. In addition, when the pore size is 0.001 μm or more, the pores are not easily crushed even when a coating is formed on the membrane surface of the substrate, and there is an advantage that the permeability to the treated water is excellent.
[0027] [Coating] Next, the coating will be described. The coating contains a crosslinked mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties. In this way, the coating contains at least two types of polymers, a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties, and thus, it is possible to provide a filtration membrane that can be mass-produced industrially, which is difficult to achieve with the technology using zwitterions, and can obtain the improved effect of fouling resistance obtained by using a polymer material having a zwitterionic structure as described above. In addition, the coating does not simply contain a hydrophilic polymer having cationic properties and a hydrophilic polymer having an anionic property, but contains a crosslinked mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having an anionic property, thereby preventing the hydrophilic polymer from falling off when filtering treated water, and maintaining high fouling resistance.
[0028] The coating may be present at least on the membrane surface that comes into contact with the treated water, but from the viewpoint of fouling resistance, it is preferable that the coating be present on the entire membrane surface.
[0029] The thickness of the coating is not particularly limited, but is preferably 0.1 nm to 10 μm, more preferably 0.5 nm to 5 μm, and most preferably 1 nm to 5 μm. When the thickness of the coating is 0.1 nm or more, the fouling suppression effect of the coating is more reliably exhibited. In addition, if the thickness of the coating is too thick, the pores of the filtration membrane, which is the base material, may be blocked, resulting in a decrease in the performance of the filtration membrane, but when the thickness of the coating is 10 μm or less, the performance of the filtration membrane can be more reliably maintained. The thickness of the coating may be observed, for example, by an electron microscope, or can be measured by surface XPS analysis or IR reflection ATR method.
[0030] (Cationic hydrophilic polymer) The hydrophilic polymer having cationic properties in this embodiment is not particularly limited, but is a hydrophilic polymer containing a cationic group in the molecular chain.
[0031] The cationic group may be contained in any of the main chain, the side chain, and the terminal. Examples of the cationic group include an ammonium group, an iminium group, a sulfonium group, and a phosphonium group. In addition, functional groups such as an amino group and an imino group, a part of which can be converted to an ammonium group or an iminium group in water, are also included in the cationic group. Among these, the cationic group is preferably an ammonium group from the viewpoint of industrial availability. As the ammonium group, any of a primary ammonium group (ammonium group), a secondary ammonium group (alkylammonium group, etc.), a tertiary ammonium group (dialkylammonium group, etc.), and a quaternary ammonium group (trialkylammonium group, etc.) can be used, but a quaternary ammonium group (trialkylammonium group, etc.) is more preferable. The hydrophilic polymer having cationic properties may contain only one type of cationic group, or may contain two or more types of cationic groups. In addition, the counter anion of the cationic group is not particularly limited, and examples thereof include a halide ion, a hydroxide ion, a phosphate ion, and a carboxylate ion. The hydrophilic polymer having cationic properties may contain only one type of counter anion, or may contain two or more types of counter anions.
[0032] The hydrophilic polymer having cationic properties is not particularly limited, and examples thereof include polyvinyl alcohol, polyethylene vinyl alcohol, polyacrylate, polymethacrylate, polymethyl methacrylate, polyacrylamide, polyvinylpyrrolidone, polyethyleneimine, polyamidine, cationized starch, and cellulose. Among these, polyvinyl alcohol containing a structure having cationic properties (hereinafter also referred to as cationic modified polyvinyl alcohol) is preferable from the viewpoints of excellent solubility in general-purpose solvents and water, low cost, and easy synthesis. In this embodiment, only one type of hydrophilic polymer having cationic properties may be used, or two or more types of hydrophilic polymers having cationic properties may be used.
[0033] The cationic hydrophilic polymer may contain the above-mentioned cationic group-containing monomer unit, and may further contain the above-mentioned cationic group-free monomer unit. In the cationic hydrophilic polymer, the content of the cationic group-containing monomer unit is preferably 0.1 mol% or more with respect to the total number (100 mol%) of the monomer units constituting the cationic hydrophilic polymer. With such a configuration, the effect of improving the fouling resistance can be more reliably obtained. The content of the cationic group-containing monomer unit is more preferably 0.5 mol% or more, and even more preferably 1 mol% or more. The upper limit of the content of the cationic group-containing monomer unit is not particularly limited as long as the shape and physical properties of the cationic hydrophilic polymer can be maintained, but is preferably 5 mol% or less.
[0034] When the hydrophilic polymer having cationic properties is a mixture of multiple hydrophilic polymers containing cationic groups, the content of monomer units having cationic groups refers to the ratio of the number of cationic monomer units to the total number of monomer units in the mixture.
[0035] The content of the monomer unit having a cationic group can be determined by NMR spectrum measurement using a proton NMR measurement device as described later in the Examples.
[0036] (Anionic hydrophilic polymer) The anionic hydrophilic polymer in this embodiment is not particularly limited, but is a hydrophilic polymer that contains an anionic group in the molecular chain.
[0037] The anionic group may be contained in the main chain, the side chain, or the terminal. Examples of the anionic group include a sulfonate group, a carboxylate group, and a phosphonate group. In addition, functional groups that can be partially converted to a sulfonate group, a carboxylate group, or a phosphonate group in water, such as a sulfonic acid group, a carboxyl group, or a phosphonic acid group, are also included in the anionic group. Among these, the anionic group is preferably a carboxyl group because of its large ionic dissociation constant. The hydrophilic polymer having anionic properties may contain only one type of anionic group, or may contain two or more types of anionic groups. In addition, the counter cation of the anionic group is not particularly limited, and examples thereof include a hydrogen ion and an alkali metal ion. The hydrophilic polymer having anionic properties may contain only one type of counter cation, or may contain two or more types of counter cations.
[0038] Examples of the hydrophilic polymer having anionic properties include, but are not limited to, polyvinyl alcohol, polyethylenevinyl alcohol, polyacrylate, polymethacrylate, polymethylmethacrylate, polyacrylamide, polyvinylpyrrolidone, polyethyleneimine, polyamidine, anionized products of starch and cellulose, etc. Among these, polyvinyl alcohol containing an anionic structure (hereinafter also referred to as anion-modified polyvinyl alcohol) is preferable from the viewpoints of excellent solubility in general-purpose solvents and water, low price, and easy synthesis. In this embodiment, only one type of hydrophilic polymer having anionic properties may be used, or two or more types of hydrophilic polymers having anionic properties may be used.
[0039] In addition, the hydrophilic polymer having anionic properties only needs to contain a monomer unit having the above-mentioned anionic group, and may further contain a monomer unit not having the above-mentioned anionic group. In the hydrophilic polymer having anionic properties, the content of the monomer unit having an anionic group is preferably 0.1 mol% or more with respect to the total number (100 mol%) of the monomer units constituting the hydrophilic polymer having anionic properties. By being 0.1 mol% or more, the effect of improving the fouling resistance can be obtained more reliably.
[0040] The content of the monomer unit having an anionic group is more preferably 0.5 mol% or more, and even more preferably 1 mol% or more. The upper limit of the content of the monomer unit having an anionic group is not particularly limited as long as the shape and physical properties of the anionic hydrophilic polymer can be maintained, but is preferably 5 mol% or less.
[0041] When the hydrophilic polymer having anionic properties is a mixture of multiple types of hydrophilic polymers containing anionic groups, the content of monomer units having anionic groups refers to the ratio of the number of anionic monomer units to the total number of monomer units in the mixture.
[0042] The content of the monomer unit having an anionic group can be determined by NMR spectrum measurement using a proton NMR measurement device as described later in the Examples.
[0043] As the hydrophilic polymer having cationic property and the hydrophilic polymer having anionic property in this embodiment, commercially available products may be used, or products produced by known synthesis methods may be used.
[0044] For example, the synthesis method of cation-modified polyvinyl alcohol and anion-modified polyvinyl alcohol is exemplified below. The synthesis method includes a method of copolymerizing a cationic or anionic monomer with a vinyl ester monomer and saponifying the copolymer by a conventional method. The vinyl ester monomer is not particularly limited as long as it is radically polymerizable, and examples thereof include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate. Among these, vinyl acetate is preferred.
[0045] Examples of methods for copolymerizing a cationic or anionic monomer with a vinyl ester monomer include known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. Among these methods, bulk polymerization performed without a solvent or solution polymerization performed using a solvent such as alcohol is usually used. When using the solution polymerization method to perform the copolymerization reaction, examples of the alcohol used as a solvent include lower alcohols such as methyl alcohol, ethyl alcohol, and propyl alcohol. Examples of initiators used in the copolymerization reaction include known initiators such as azo initiators such as 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethyl-valeronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(N-butyl-2-methylpropionamide); and peroxide initiators such as benzoyl peroxide and n-propyl peroxycarbonate. The polymerization temperature during the copolymerization reaction is not particularly limited, but a range of 5°C to 180°C is appropriate.
[0046] The vinyl ester polymer obtained by copolymerizing a cationic or anionic monomer with a vinyl ester monomer is then saponified in a solvent according to a known method to give a cationically modified polyvinyl alcohol or an anionically modified polyvinyl alcohol.
[0047] An alkaline substance is usually used as a catalyst for the saponification reaction of vinyl ester polymers, and examples of such catalysts include alkali metal hydroxides such as potassium hydroxide and sodium hydroxide, and alkali metal alkoxides such as sodium methoxide. The saponification catalyst may be added all at once at the beginning of the saponification reaction, or a portion of the catalyst may be added at the beginning of the saponification reaction, and the remainder may be added in the middle of the saponification reaction. Examples of solvents used in the saponification reaction include methanol, methyl acetate, dimethyl sulfoxide, diethyl sulfoxide, and dimethylformamide. Among these solvents, methanol is preferred. The saponification reaction can be carried out in either a batch method or a continuous method. After the saponification reaction is completed, the remaining saponification catalyst may be neutralized as necessary, and examples of neutralizing agents that can be used include organic acids such as acetic acid and lactic acid, and ester compounds such as methyl acetate.
[0048] The degree of saponification of the cation-modified polyvinyl alcohol and the anion-modified polyvinyl alcohol is not particularly limited, but is preferably 40 to 99.9 mol%. If the degree of saponification is less than 40 mol%, the crystallinity may decrease and the strength of the filtration membrane may be insufficient. The degree of saponification is more preferably 60 mol% or more, and even more preferably 80 mol% or more. Usually, the degree of saponification is 99.9 mol% or less. In this case, when the polyvinyl alcohol is a mixture of multiple types of polyvinyl alcohol, the degree of saponification refers to the average degree of saponification of the entire mixture. The degree of saponification of polyvinyl alcohol is a value measured in accordance with JIS K6726.
[0049] The viscosity average degree of polymerization (hereinafter also simply referred to as the degree of polymerization) of the cation-modified polyvinyl alcohol and the anion-modified polyvinyl alcohol is not particularly limited, but is preferably 50 to 10,000. If the degree of polymerization is less than 50, the coating may not maintain sufficient strength for practical use. It is more preferable that the degree of polymerization is 100 or more. If the degree of polymerization exceeds 10,000, the viscosity of the polymer aqueous solution is too high, making it difficult to apply the polymer aqueous solution uniformly, and the obtained film may be prone to defects. It is more preferable that the degree of polymerization is 8,000 or less. In this case, when the polyvinyl alcohol is a mixture of multiple types of polyvinyl alcohol, the degree of polymerization refers to the average degree of polymerization of the entire mixture. The viscosity average degree of polymerization of polyvinyl alcohol is a value measured in accordance with JIS K6726.
[0050] (Mixture of hydrophilic polymers with cationic and anionic properties) The filtration membrane in this embodiment has a coating containing a crosslinked mixture of a hydrophilic polymer having cationic properties as described above and a hydrophilic polymer having anionic properties as described above, at least on the membrane surface that contacts the treated water. If only one of the hydrophilic polymers is used, there is a problem that the effect of the pseudo zwitterion cannot be obtained. In addition, the coating may contain at least one hydrophilic polymer having cationic properties and at least one hydrophilic polymer having anionic properties, and may contain, for example, two or more hydrophilic polymers having cationic properties and at least two or more hydrophilic polymers having anionic properties, and the types are not particularly limited.
[0051] In the mixture, the ratio of the hydrophilic polymer having cationic properties to the hydrophilic polymer having anionic properties is influenced by the molecular weight of the hydrophilic polymer having cationic properties, the molar ratio and structure of the cationic structure, the molecular weight of the hydrophilic polymer having anionic properties, the molar ratio and structure of the anionic structure, etc., and cannot be uniquely defined, but is preferably 2:98 to 98:2 in mass ratio. By having a ratio in such a range, there is an advantage that a pseudo zwitterion effect (fouling resistance) can be obtained more reliably. The ratio of the hydrophilic polymer having cationic properties to the hydrophilic polymer having anionic properties is more preferably 3:97 to 97:3 in mass ratio, and even more preferably 5:95 to 95:5.
[0052] In addition, the degree of crosslinking of the mixture of the cationic hydrophilic polymer and the anionic hydrophilic polymer is not particularly limited. The degree of crosslinking of the mixture of the cationic hydrophilic polymer and the anionic hydrophilic polymer can be, for example, a degree of crosslinking such that the cationic hydrophilic polymer and the anionic hydrophilic polymer are not detected in the filtrate when water is passed through a filtration membrane having the coating. The degree of the cationic hydrophilic polymer and the anionic hydrophilic polymer are not detected will be specifically described below.
[0053] First, pure water is passed through the filtration membrane having the coating to perform flushing cleaning, and then a 40% by volume aqueous ethanol solution is circulated through the washed filtration membrane at 40°C for 1 hour. The concentrations of the cationic hydrophilic polymer and the anionic hydrophilic polymer in the circulated aqueous ethanol solution are measured. From these hydrophilic polymers and the membrane area of the filtration membrane used, the concentrations of the cationic hydrophilic polymer and the anionic hydrophilic polymer per m2 of membrane area are calculated. 2 The amount of extraction per unit area of membrane is calculated. 2The amount of extraction per unit time is preferably 300 mg or less, more preferably 100 mg or less, and even more preferably 10 mg or less. When the amount of extraction is 300 mg or less, it can be considered that the crosslinking is sufficient to obtain the effects of the present invention.
[0054] The content of the crosslinked body relative to the entire filtration membrane is not particularly limited, but is preferably 0.1 to 15 mass%, more preferably 0.1 to 10 mass%, and even more preferably 0.5 to 10 mass%, relative to the mass of the filtration membrane. When the content of the crosslinked body is 0.1 mass% or more, the hydrophilicity of the filtration membrane is sufficiently increased and the fouling resistance is improved. When the content of the crosslinked body is 15 mass% or less, deterioration in performance, such as a decrease in the water permeability of the membrane due to pore clogging of the membrane, can be suppressed.
[0055] The method for measuring the content of the crosslinked body is not particularly limited. For example, the content of the crosslinked body in the filtration membrane can be calculated by dissolving and extracting the resin of the filtration membrane itself with a solvent and then measuring the dry weight of the remaining undissolved matter.
[0056] In addition, the coating in this embodiment may contain a crosslinked mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties, and may be made of the crosslinked mixture, or may further contain a hydrophilic polymer having cationic properties that is not crosslinked, or a hydrophilic polymer having anionic properties that is not crosslinked. In addition, it may contain a polyfunctional amine compound or a polyfunctional acid halide compound. For example, the polyfunctional amine compound is not particularly limited as long as it has two or more amino groups in the molecule. Examples of the polyfunctional amine compound include an aromatic polyfunctional amine compound, an aliphatic polyfunctional amine compound, and an alicyclic polyfunctional amine compound. Examples of the aromatic polyfunctional amine compound include phenylenediamines such as m-phenylenediamine, p-phenylenediamine, and o-phenylenediamine, triaminobenzenes such as 1,3,5-triaminobenzene and 1,3,4-triaminobenzene, diaminotoluenes such as 2,4-diaminotoluene and 2,6-diaminotoluene, 3,5-diaminobenzoic acid, xylylenediamine, and 2,4-diaminophenol dihydrochloride (amidol). The polyfunctional acid halide compound (polyfunctional acid halide) is not particularly limited as long as it is a compound obtained by removing two or more hydroxyl groups from an acid contained in a polyfunctional organic acid compound having two or more acids such as carboxylic acid in the molecule, and a halogen is bonded to the acid from which the hydroxyl groups have been removed. Examples of the polyfunctional acid halide compound include trimesic acid trichloride, terephthalic acid dichloride, isophthalic acid dichloride, biphenyldicarboxylic acid dichloride, naphthalenedicarboxylic acid dichloride, benzenetrisulfonic acid trichloride, and benzenedisulfonic acid dichloride.
[0057] [Water contact angle of filtration membrane] The water contact angle of the membrane surface of the filtration membrane in this embodiment is preferably smaller than 90°. If the water contact angle is smaller than 90°, it is considered that the hydrophilicity of the filtration membrane is sufficiently maintained, and high anti-fouling properties can be obtained more reliably. The water contact angle is more preferably smaller than 88°, and even more preferably smaller than 86°. The value of the water contact angle is obtained by dropping a water droplet on the filtration membrane, taking an image at that moment, and measuring the angle (water contact angle) between the water droplet surface and the surface of the filtration membrane. In addition, Drop Master 700 manufactured by Kyowa Interface Science Co., Ltd. can be used as a measuring device.
[0058] [Zeta potential of filtration membrane] The zeta potential of the membrane surface of the filtration membrane in this embodiment is preferably -5 mV or more and +15 mV or less. It is considered that the cationic and anionic structures are formed in a well-balanced manner on the membrane surface by the zeta potential being within the above range, and the pseudo zwitterion effect (fouling resistance) can be obtained more reliably. For example, when the zeta potential is -10 mV, the number of anionic structures is too large on the membrane surface, and the surface properties are closer to anionic rather than zwitterionic. The zeta potential is more preferably -5 mV or more and +10 mV or less, and even more preferably -5 mV or more and +8 mV or less. The zeta potential can be measured using a zeta potential / particle measurement system ELSZ-1000ZS by Otsuka Electronics Co., Ltd.
[0059] <Membrane filtration manufacturing method> The method for producing a filtration membrane in this embodiment includes a preparation step of preparing a coating solution containing a mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties, a coating formation step of contacting at least a membrane surface of a filtration membrane (substrate) for water treatment, which is in contact with the treatment water, with the coating solution to form a coating on the membrane surface, and a crosslinking step of crosslinking the mixture of the hydrophilic polymer having cationic properties and the hydrophilic polymer having anionic properties after the coating formation step.
[0060] [Preparation process] The preparation step is not particularly limited as long as it is possible to prepare a coating solution containing a mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties. For example, the preparation step is a step of dissolving a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties in a solvent to prepare a coating solution in which at least two types of hydrophilic polymers are dissolved.
[0061] The solvent is not particularly limited, but is preferably a solvent that is unlikely to adversely affect a general filtration membrane when forming a coating on the filtration membrane. Specifically, hydrophilic solvents such as water, ethylene glycol, glycerin, ethanol, and methanol, and amphiphilic solvents such as dimethylacetamide, dimethylformamide, γ-butyrolactone, ε-caprolactone, and N-methylpyrrolidone are preferred. Among these, water is preferred because it is the target of filtration by the filtration membrane and has the least effect on the filtration membrane.
[0062] The cationic hydrophilic polymer and the anionic hydrophilic polymer may be the same as those exemplified in the above [Coating]. These may be synthesized by a known method or may be commercially available.
[0063] The mixing ratio of the hydrophilic polymer having cationic properties to the hydrophilic polymer having anionic properties is preferably 2:98 to 98:2, more preferably 3:97 to 97:3, and further preferably 5:95 to 95:5.
[0064] [Film formation process] The coating film forming step is not particularly limited as long as the coating film solution prepared in the preparation step is brought into contact with at least the membrane surface of the substrate, which is in contact with the treatment water, to form a coating film on the membrane surface. The substrate is a filtration membrane for water treatment, and examples thereof include those similar to those exemplified in the above-mentioned [Substrate].
[0065] In the coating film forming step, the method of contacting the membrane surface with the coating film solution is not particularly limited, and for example, in the manufacturing process of a filtration membrane (substrate), the coating film solution is dissolved in a coagulation bath of the filtration membrane (substrate) to bring the membrane surface into contact. According to this method, the coating film can be formed at the same time as the manufacturing of the filtration membrane (substrate). In addition, a commercially available filtration membrane or a filtration membrane that has already been manufactured can be used as the substrate, and the substrate can be contacted by immersing the filtration membrane in the coating film solution.
[0066] When the substrate is a hollow fiber membrane, the coating solution is poured into the hollow portion (inside) during molding of the hollow fiber membrane, and the hollow portion (inside) is washed with water and diffused and washed from the hollow portion (inside) to the outside, thereby enabling the hollow portion (inside) to be uniformly contacted with the coating solution from the hollow portion (inside) to the outer periphery.
[0067] Furthermore, when the membrane surface is brought into contact with the coating solution, it is preferable that the coating solution is brought into contact with at least the surface of the substrate that comes into contact with the treatment water, and that the coating solution is adhered to the membrane surface.
[0068] [Crosslinking process] The crosslinking step is not particularly limited as long as it can crosslink the mixture of the cationic hydrophilic polymer and the anionic hydrophilic polymer after the coating step. As a method of crosslinking, for example, when a polyvinyl alcohol copolymer is used, it is preferable to acetalize the substrate after contact with the coating solution to make it insoluble in hot water. The acetalization can be performed by treating the substrate after contact with the coating solution in an acid aqueous solution containing an aldehyde compound. The aldehyde includes aldehydes such as formaldehyde, glyoxal, glutaraldehyde, malondialdehyde, and nonanedial, and the acid is preferably a strong acid such as sulfuric acid, hydrochloric acid, or nitric acid. In addition, for example, when a polyvinylpyrrolidone copolymer is used, it is preferable to make the substrate insoluble in hot water by crosslinking with a polymerization initiator after contacting the substrate with the coating solution. As the polymerization initiator, for example, oxidizing agents such as hydrogen peroxide, sodium persulfate, potassium persulfate, etc., acids such as sulfuric acid, nitric acid, hydrochloric acid, etc., bases such as sodium hydroxide, potassium hydroxide, etc., ultraviolet light, etc. can be used. EXAMPLES
[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0070] [Example 1] First, the base material, the cationic hydrophilic polymer, and the anionic hydrophilic polymer used in Example 1 will be described.
[0071] (base material) A polyvinylidene fluoride hollow fiber filtration membrane (M02-100, manufactured by Kuraray Co., Ltd.) was prepared as a substrate. The pore size of this hollow fiber filtration membrane was 0.02 μm. In addition, this hollow fiber filtration membrane is a hollow part of which a commercially available polyvinyl alcohol (Kuraray Poval 5-88, manufactured by Kuraray Co., Ltd.) that has not been modified is placed in the hollow part during molding of the hollow fiber, washed with water, and diffused and washed from the hollow part to the outside, so that the hollow part to the outer periphery is uniformly contacted with the polyvinyl alcohol, and the surface of the hollow fiber membrane is already coated with unmodified polyvinyl alcohol.
[0072] (Cationic hydrophilic polymer) As the hydrophilic polymer having cationic properties, a cation-modified polyvinyl alcohol synthesized by the following method was used.
[0073] A 6L separable flask equipped with a stirrer, a temperature sensor, a dropping funnel and a reflux condenser was charged with 2156g of vinyl acetate, 644g of methanol and 60.8g of a methanol solution containing 20% by mass of methacrylamide propyl trimethyl ammonium chloride. The system was replaced with nitrogen under stirring, and the temperature in the system was raised to 60°C. 0.8g of 2,2'-azobisisobutyronitrile was added to this system to start the polymerization reaction. After the polymerization reaction was carried out for 4 hours while adding 290g of a methanol solution containing 20% by mass of methacrylamide propyl trimethyl ammonium chloride to the system from the start of the polymerization, the polymerization reaction was stopped. Next, unreacted vinyl acetate monomer was expelled by introducing methanol vapor into the system, and a methanol solution containing 55% by mass of vinyl ester copolymer was obtained.
[0074] To a methanol solution containing 55% by mass of this vinyl ester copolymer, methanol and a methanol solution containing 10% by mass of sodium hydroxide were added in this order under stirring so that the molar ratio of sodium hydroxide to the vinyl acetate units in the copolymer was 0.01 and the solid content concentration of the vinyl ester copolymer was 30% by mass, and the saponification reaction was initiated at 40°C.
[0075] Immediately after the gelation reaction proceeded, the gel was removed from the reaction system and crushed. Then, one hour after the gelation reaction, methyl acetate was added to the crushed product to neutralize it, and a swollen cationic polymer of poly(vinyl alcohol-methacrylamidopropyltrimethylammonium chloride) was obtained. Methanol was added to the swollen cationic polymer in an amount six times by mass (six times the bath ratio), and the polymer was washed under reflux for one hour, and the polymer was filtered. The polymer was dried at 65°C for 16 hours to obtain a cation-modified polyvinyl alcohol. The content of monomer units having a cationic group (i.e., the proportion of monomer units of methacrylamidepropyltrimethylammonium chloride) was determined from proton NMR spectrum measurement, and it was confirmed that the content was 2 mol% relative to the total number of monomer units. The degree of polymerization was 1700, and the degree of saponification was 88.2 mol%.
[0076] The content of monomer units having a cationic group was determined by dissolving the polymer in a heavy water solvent as a measurement sample, and determining the ratio (mol %) of the number of methacrylamide propyl trimethyl ammonium chloride monomer units to the total number of monomer units in the polymer from NMR spectrum measurement using a 500 MHz proton NMR measurement device (GX-500, manufactured by JEOL).
[0077] (Anionic hydrophilic polymer) As the hydrophilic polymer having anionic properties, anion-modified polyvinyl alcohol synthesized by the following method was used.
[0078] A 6-liter reactor equipped with a reflux condenser, a stirrer, a thermometer, a nitrogen inlet, a feed port for a post-addition liquid, and a pump was charged with 2400 g of vinyl acetate, 600 g of methanol, 2.2 g of itaconic acid, and 150 g of acetaldehyde. The polymerization liquid was stirred while the system was replaced with nitrogen. The polymerization liquid was heated, and when it reached a constant temperature of 60°C, 4.5 g of 2,2'-azobisisobutyronitrile was added to start the polymerization. From the start of the polymerization, 320 g of a methanol solution containing 25% by weight of itaconic acid was added to the system while the reaction was continued, and the polymerization was stopped after 5 hours. The obtained polymerization paste was dropped into n-hexane to precipitate the polymer. The precipitated polymer was collected, dissolved in acetone, and precipitated in n-hexane, and a reprecipitation-purification operation was performed three times. The polymer was further dissolved in acetone and dropped into distilled water, boiled and purified, and then dried at 60°C to obtain a vinyl ester copolymer.
[0079] Next, a 45% methanol solution of vinyl ester copolymer was prepared. While stirring this purified vinyl ester copolymer methanol solution at 40°C, a 10% methanol solution of sodium hydroxide was added so that the molar ratio of sodium hydroxide to vinyl acetate unit in the copolymer was 0.045, and a saponification reaction was carried out for 60 minutes.
[0080] Immediately after the gelation reaction proceeded, the gel was removed from the reaction system and crushed. Then, one hour after the gelation reaction, the crushed product was neutralized by adding methyl acetate to obtain a swollen anionic polymer of poly(vinyl alcohol-itaconic acid). Six times the mass of the swollen anionic polymer (six times the bath ratio) was added to the polymer, which was washed under reflux for one hour, and the polymer was filtered. The polymer was dried at 65°C for 16 hours to obtain an anion-modified polyvinyl alcohol. The content of the monomer unit having an anionic group (i.e., the proportion of the monomer unit of itaconic acid) was determined by proton NMR spectrum measurement, and it was confirmed that the content was 2 mol% relative to the total number of monomer units. The content of the monomer unit having an anionic group was determined by the same method as the content of the monomer unit having a cationic group. The degree of polymerization was 300, and the degree of saponification was 88.0 mol%.
[0081] (Production of filtration membranes) As a coating solution, 4.75 g of the cation-modified polyvinyl alcohol obtained by the above method and 0.25 g of the anion-modified polyvinyl alcohol obtained by the above method were dissolved in 1 liter of water to prepare a 0.5 wt% aqueous solution (coating solution) containing the cation-modified polyvinyl alcohol and the anion-modified polyvinyl alcohol. At this time, the mass ratio of the cation-modified polyvinyl alcohol to the anion-modified polyvinyl alcohol was 95% and 5%.
[0082] Next, the above-mentioned substrate was immersed in the coating solution for about 1 hour, and the film surface of the substrate that was in contact with the treatment water was brought into contact with the coating solution. After that, in order to remove the excess coating solution, the substrate was washed with water for 10 minutes to remove the excess coating solution.
[0083] Thereafter, the substrate that had been in contact with the coating solution was immersed in an aqueous solution containing 5 g / L glutaraldehyde and 50 g / L sulfuric acid at 40° C. for 30 minutes to crosslink the cation-modified polyvinyl alcohol and the anion-modified polyvinyl alcohol and to make them insoluble in water. In this way, a filtration membrane was obtained having a coating containing a crosslinked mixture of a cationic hydrophilic polymer and an anionic hydrophilic polymer on at least the membrane surface that contacts the treatment water.
[0084] (Water contact angle of filtration membrane) The water contact angle of the membrane surface of the obtained filtration membrane was 83°, and it was confirmed that the membrane was hydrophilic. The water contact angle was measured by dropping a water droplet on the filtration membrane and taking an image at that moment. The angle between the water droplet surface and the surface of the filtration membrane was then measured. This angle was the water contact angle. The measurement device used was Drop Master 700 manufactured by Kyowa Interface Science Co., Ltd.
[0085] (Zeta potential of filtration membrane) In addition, the zeta potential of the membrane surface of the obtained filtration membrane was +6 mV, confirming that a well-balanced cationic and anionic structure was formed on the membrane surface. The zeta potential was measured using a zeta potential / particle measurement system ELSZ-1000ZS manufactured by Otsuka Electronics Co., Ltd.
[0086] (Confirmation of cross-linking) In addition, whether the mixture of the hydrophilic polymer having cationic properties and the hydrophilic polymer having anionic properties contained in the coating of the produced filtration membrane was crosslinked was confirmed by the following method.
[0087] After flushing and cleaning the filtration membrane by running pure water through it, a 40% by volume aqueous solution of ethanol was circulated through the washed filtration membrane at 40°C for 1 hour. The concentrations of the cationic hydrophilic polymer and the anionic hydrophilic polymer in the circulated aqueous solution of ethanol were measured. From these hydrophilic polymers and the membrane area of the prepared filtration membrane, the concentration of the hydrophilic polymer with a membrane area of 1 m2 was calculated. 2 The amount of cationic hydrophilic polymers and anionic hydrophilic polymers extracted per 1 m of membrane area is calculated as follows: 2The amount of extraction was 5 mg per unit area, and since this amount of extraction was sufficiently small, it was confirmed that crosslinking had occurred. In addition, when the amount of extraction is sufficiently small, it can be considered that the entire amount of the hydrophilic polymer having cationic property and the hydrophilic polymer having anionic property contained in the coating film have been crosslinked.
[0088] (Crosslinked Body Content) Furthermore, the content of the crosslinked body of the mixture of the cationic hydrophilic polymer and the anionic hydrophilic polymer relative to the entire filtration membrane was calculated by completely dissolving and extracting the polyvinylidene fluoride, which is the material of the filtration membrane, with dimethylformamide, and then measuring the dry weight of the remaining undissolved matter. The content of the crosslinked body calculated in this way was 3 mass% relative to the entire filtration membrane.
[0089] [Example 2] A filtration membrane having a coating containing a crosslinked mixture of a cationic hydrophilic polymer and an anionic hydrophilic polymer on at least the membrane surface in contact with the treatment water was obtained in the same manner as in Example 1, except that the coating solution was prepared as follows.
[0090] As a coating solution, 4 g of cation-modified polyvinyl alcohol (the same as that used in Example 1) and 1 g of anion-modified polyvinyl alcohol (the same as that used in Example 1) were dissolved in 1 liter of water to prepare a 0.5 wt% aqueous solution (coating solution) containing cation-modified polyvinyl alcohol and anion-modified polyvinyl alcohol. At this time, the mass ratio of the cation-modified polyvinyl alcohol to the anion-modified polyvinyl alcohol was 80% and 20%.
[0091] The water contact angle and zeta potential of the membrane surface of the obtained filtration membrane were measured in the same manner as in Example 1, and the water contact angle was 83° and the zeta potential was −3 mV.
[0092] Furthermore, using the same method as in Example 1, it was confirmed whether the mixture of the cationic hydrophilic polymer and the anionic hydrophilic polymer contained in the coating was crosslinked. 2 The amount of extraction was 6 mg per unit area, confirming that crosslinking had occurred. In addition, when the amount of extraction is sufficiently small, it can be considered that the entire amount of the hydrophilic polymer having cationic property and the hydrophilic polymer having anionic property contained in the coating film have been crosslinked.
[0093] Furthermore, the content of crosslinked bodies in a mixture of a cationic hydrophilic polymer and an anionic hydrophilic polymer was measured in the same manner as in Example 1, and the content of crosslinked bodies relative to the entire filtration membrane was found to be 5 mass%.
[0094] [Comparative Example 1] The polyvinylidene fluoride hollow fiber filtration membrane (M02-100, manufactured by Kuraray Co., Ltd.) used as the substrate in Example 1 was prepared and used as the filtration membrane in Comparative Example 1. That is, the filtration membrane in Comparative Example 1 is a hollow fiber membrane whose membrane surface is simply coated with unmodified polyvinyl alcohol, and does not have a coating containing a crosslinked product of a mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties.
[0095] The water contact angle and zeta potential of the membrane surface of this filtration membrane were measured in the same manner as in Example 1, and the water contact angle was 87° and the zeta potential was −8 mV.
[0096] Furthermore, pure water was passed through the filtration membrane to perform flushing cleaning, and then a 40% by volume aqueous ethanol solution was circulated through the washed filtration membrane at 40°C for 1 hour. The concentration of unmodified polyvinyl alcohol in the circulated aqueous ethanol solution was measured. From the unmodified polyvinyl alcohol and the membrane area of the prepared filtration membrane, the concentration of unmodified polyvinyl alcohol per m2 of membrane area was calculated. 2 The amount of unmodified polyvinyl alcohol extracted per unit area of membrane is calculated as follows: 2The amount of extraction per unit time was 500 mg, which confirmed that the unmodified polyvinyl alcohol was not crosslinked.
[0097] In addition, the content of crosslinked bodies in the mixture of the cationic hydrophilic polymer and the anionic hydrophilic polymer was measured in the same manner as in Example 1. As a result, the content of crosslinked bodies relative to the entire filtration membrane was 0 mass%.
[0098] Table 1 shows the material of the hollow fiber membranes used in Examples 1 and 2 and Comparative Example 1, the cationic hydrophilic polymer, the content of monomer units having a cationic group, the anionic hydrophilic polymer, the content of monomer units having an anionic group, the mass ratio of the cationic hydrophilic polymer to the anionic hydrophilic polymer, the water contact angle of the obtained filtration membrane, whether the mixture of the cationic hydrophilic polymer and the anionic hydrophilic polymer is crosslinked (○ if crosslinked, × if not crosslinked), and the zeta potential.
[0099] [Table 1]
[0100] [Evaluation of filtration membranes] Filtration experiments were carried out on the filtration membranes of Example 1, Example 2, and Comparative Example 1.
[0101] The raw water was river drift water (turbidity 5 mg / L) to which 30 mg / L of polyaluminum chloride (PAC700A manufactured by Taki Chemical Industry Co., Ltd.) was added as a coagulant, and the filterability was evaluated at a filtration flow rate of 6.0 m / d. The hollow fiber filtration membranes in Examples 1 and 2 and Comparative Example 1 had a membrane area of 0.00254 m 2 A miniature element was created (30cm effective length x 3 pieces), and physical cleaning was periodically performed every 30 minutes of filtration using back pressure cleaning with 0.19MPa air and vibration with bubbling, and the effect of this on fouling resistance was evaluated. The evaluation results are shown in Figure 1.
[0102] As a result of the above evaluation, in Examples 1 and 2, the fouling suppression effect was observed and stable operation over a long period of time was possible, whereas in Comparative Example 1, the pressure (transmembrane pressure difference) rose immediately after filtration began and operation was not successful (Figure 1).
[0103] From the above results, it was confirmed that the filtration membranes (Examples 1 and 2) having a coating containing a crosslinked mixture of a cationic hydrophilic polymer and an anionic hydrophilic polymer on at least the membrane surface that comes into contact with the treated water have excellent fouling resistance.
Claims
1. A filtration membrane for water treatment, A filtration membrane having a coating containing a crosslinked mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having an anionic property, at least on the membrane surface that comes into contact with the treated water.
2. the hydrophilic polymer having cationic properties contains a monomer unit having a cationic group in a molecular chain, and the content of the monomer unit having the cationic group is 0.1 mol % or more relative to the total number (100 mol %) of monomer units constituting the hydrophilic polymer having cationic properties; 2. The filtration membrane according to claim 1, wherein the hydrophilic polymer having anionic properties contains a monomer unit having an anionic group in a molecular chain, and the content of the monomer unit having an anionic group is 0.1 mol % or more relative to the total number (100 mol %) of monomer units constituting the hydrophilic polymer having anionic properties.
3. the hydrophilic polymer having cationic properties is a cationically modified polyvinyl alcohol, The filtration membrane according to claim 1 , wherein the hydrophilic polymer having anionic properties is an anion-modified polyvinyl alcohol.
4. The filtration membrane according to claim 1, wherein the zeta potential of the membrane surface having the coating is -5 mV or more and 15 mV or less.
5. The filtration membrane according to claim 1, wherein a ratio of the hydrophilic polymer having cationic property to the hydrophilic polymer having anionic property in the mixture is 2:98 to 98:2 in terms of mass ratio.
6. A preparation step of preparing a coating solution containing a mixture of a hydrophilic polymer having cationic properties and a hydrophilic polymer having anionic properties; a coating forming step of contacting at least a membrane surface of a water treatment filtration membrane, the membrane surface being in contact with the coating solution, to form a coating on the membrane surface; A method for producing a filtration membrane, comprising: a crosslinking step of crosslinking the mixture of the hydrophilic polymer having cationic property and the hydrophilic polymer having anionic property after the coating step.
Citation Information
Patent Citations
Polymer additives containing zwitterionic moieties for PVDF-based membranes
JP2023506230A
Hydrophilised vinylidene fluoride-based porous hollow fibre membrane, and manufacturing method therefor
WO2015008668A1